Loading web-font TeX/Math/Italic

9x+5=4(x+2)x

Simple and best practice solution for 9x+5=4(x+2)x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+5=4(x+2)x equation:



9x+5=4(x+2)x
We move all terms to the left:
9x+5-(4(x+2)x)=0
We calculate terms in parentheses: -(4(x+2)x), so:
4(x+2)x
We multiply parentheses
4x^2+8x
Back to the equation:
-(4x^2+8x)
We get rid of parentheses
-4x^2+9x-8x+5=0
We add all the numbers together, and all the variables
-4x^2+x+5=0
a = -4; b = 1; c = +5;
Δ = b2-4ac
Δ = 12-4·(-4)·5
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
x_{1}=\frac{-b-\sqrt{\Delta}}{2a}
x_{2}=\frac{-b+\sqrt{\Delta}}{2a}

\sqrt{\Delta}=\sqrt{81}=9
x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-9}{2*-4}=\frac{-10}{-8} =1+1/4
x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+9}{2*-4}=\frac{8}{-8} =-1

See similar equations:

| -5(5y+-7)=-15 | | 4(-5n+2)=-5n-37 | | 4=30+2x | | -2(2x-1)=-4x+2 | | −5c2+c−18=  −6c2−6c2 | | Y=x+2/3 | | -3/5x-2=10 | | -5(k-8)=-2(8k+2) | | 4×v×6=30 | | N-4+2n=-4 | | 112n^2-567=0 | | 28=-7/3v | | −5=n/2 | | 10=x+4/8 | | −8x2−3x−8=0−8x2−3x−8=0 | | 10(v+2)-4v=2(3v+1)-3 | | 6x+7500=51900 | | 4x+4=-64 | | n/15=10-4 | | −5=n2 | | 10a+9=-9 | | 2x-4+8=9x+4x-84 | | 2=n|2+6 | | 6/11x-7=-25 | | 38+3r=10r | | 5x+30=1540 | | 11=4x-23 | | -3+2x=-12-3x | | 6(n=5)=2 | | 3x-2300=42700 | | 3x-5+91=203 | | 3b-2+7b-12-2b+14=0 |

Equations solver categories